Metal composite material and preparation method and application thereof
By covering the second metal on the metal surface and using microwave treatment, the problem of reducing conductivity of metal conductive materials under humid and heat conditions is solved, and a metal composite material with lower resistivity and high temperature stability is achieved, suitable for conductive materials , semiconductor and photovoltaic fields.
Patent Information
- Application Number
- CN202411765618.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, metal conductive materials are prone to electromigration under wet and heat conditions, resulting in a decrease in conductivity. The chemical vapor deposition method is complex in process, has high energy consumption and is not suitable for the treatment of high melting point and special-shaped materials.
Using a metal composite material, by covering the second metal on the surface of the first metal, the mass content is 3-70%, and mixing the aqueous solution containing the first metal with the solution containing the second metal compound by microwave treatment. Microwave treatment is performed to improve conductivity and stability.
A more uniform coating is achieved, reducing resistivity, improving chemical stability at high temperatures, and enhancing conductive properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material preparation, and in particular to a metal composite material and a preparation method and application thereof. Background Art
[0002] Conductive materials are an important driving force for the development of modern science and industry due to their wide application in electronic devices, communication technology, energy and materials science. Conductive materials are divided into two categories, metal conductors and non-metallic conductors. The conductivity of metal conductors comes from the free electrons they have, while the conductivity of non-metallic conductors comes from their electronic structure and chemical bonds. The physical properties of conductive materials are crucial to their performance and effects in various applications. The most important of these are conductivity and stability. The conductivity of conductive materials needs to meet requirements to support various operations and functions, such as processing information, converting signals and storing data. Stability refers to the ability of conductive materials to maintain their electrical properties under different environments, such as high temperature resistance and corrosion resistance.
[0003] With the rapid development of science and technology fields such as integrated circuits, electronic information communications, and solar cells, the miniaturization, chip-type, and multi-layer processes of electronic components have accelerated, and the demand for electronic pastes with metal powders such as silver, gold, platinum, nickel, and copper as the main functional phase is also increasing. Electronic pastes with good antioxidant properties and excellent electrical properties have become the preferred materials. As a widely used electronic paste, silver-based electronic pastes have excellent conductivity and good shielding effect (up to 65 dB or more). However, metallic silver is expensive, and silver ions will produce electromigration under hot and humid conditions, which will lead to increased coating resistance and reduced conductivity. Metallic copper is cheap and has good electrical properties, but its oxidation stability is poor and it is easily oxidized and loses conductivity, so it cannot directly become a conductive phase filler for conductive pastes.
[0004] In the prior art, the methods for coating other substances on the surface of materials usually include chemical vapor deposition (CVD), physical vapor deposition (PVD), melt atomization, chemical plating, mechanical ball milling, etc. Chemical vapor deposition (CVD) uses the principle of gas phase reaction at high temperature to deposit a layer of highly conductive material on the surface of the material, thereby improving the conductivity of the overall material. However, the chemical vapor deposition method has a complex material processing process, high energy consumption, and general uniformity, and is not suitable for depositing materials with high melting points and special shapes. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a metal composite material and a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a metal composite material, comprising a first metal and a second metal coated on the surface of the first metal; in the metal composite material, the mass content of the second metal is 3-70%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any value therebetween.
[0007] In some embodiments, in the metal composite material, the mass content of the second metal is 10-65%, preferably 15-55%, and more preferably 25-50%.
[0008] In some embodiments, the mass ratio of the second metal to the first metal is 0.01-2, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2 or any value therebetween.
[0009] In some embodiments, the mass ratio of the second metal to the first metal is 0.05-1.2.
[0010] In some embodiments, the mass ratio of the second metal to the first metal is 0.1-0.8.
[0011] In some embodiments, the resistivity of the metal composite material is 15-70 μΩ·cm, for example, 20 μΩ·cm, 25 μΩ·cm, 30 μΩ·cm, 35 μΩ·cm, 40 μΩ·cm, 45 μΩ·cm, 50 μΩ·cm, 55 μΩ·cm, 60 μΩ·cm, 65 μΩ·cm, 70 μΩ·cm or any value therebetween.
[0012] In some embodiments, the metal composite material has a resistivity of 15-30 μΩ·cm.
[0013] In some embodiments, the resistivity of the metal composite material after calcination at 200°C is 15-100μΩ·cm, for example, 17μΩ·cm, 20μΩ·cm, 23μΩ·cm, 26μΩ·cm, 29μΩ·cm, 32μΩ·cm, 35μΩ·cm, 38μΩ·cm, 45μΩ·cm, 50μΩ·cm, 60μΩ·cm, 70μΩ·cm, 80μΩ·cm, 90μΩ·cm, or 100μΩ·cm.
[0014] In some embodiments, the resistivity of the metal composite material after calcination at 200° C. is 20-60 μΩ·cm.
[0015] In some embodiments, the resistivity of the metal composite material after calcination at 200° C. is 20-40 μΩ·cm.
[0016] In some embodiments, the first metal is selected from one or more of aluminum, zinc, nickel, bismuth, or copper.
[0017] In some embodiments, the second metal is selected from one or more of nickel, zinc, manganese, gold or silver.
[0018] In some embodiments, the second metal is selected from one or more of nickel, zinc, gold, or silver.
[0019] In a second aspect, the present invention provides a method for preparing the metal composite material described in the third aspect of the present invention, comprising the following steps: coating an aqueous solution containing a first metal and a solution containing a second metal compound under microwave treatment.
[0020] In some embodiments, the second metal compound is selected from one or more of nitrates, nitrites, sulfates, sulfoxylates, chlorates, hypochlorites, perchlorates, acetates, carbonates, bicarbonates, oxalates, aluminates, silicates, metasilicates, chlorides, sulfides, oxides or hydroxides of the second metal.
[0021] In some embodiments, the mass ratio of the second metal salt to the first metal is 0.01-2, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2 or any value therebetween.
[0022] In some embodiments, the mass ratio of the second metal compound to the first metal is 0.05-1.2.
[0023] In some embodiments, the mass ratio of the second metal compound to the first metal is 0.1-0.8.
[0024] In some embodiments, the preparation method comprises the following steps: S1, mixing an aqueous solution containing a first metal, a dispersant, a buffer, a pH adjuster, and a film-forming agent to obtain a suspension; S2, mixing a solution containing a second metal compound, a reducing agent and the suspension and subjecting the mixture to microwave treatment.
[0025] In some embodiments, the buffer is selected from ammonium sulfate.
[0026] In some embodiments, the pH adjuster is selected from aqueous ammonia.
[0027] In some embodiments, the mass concentration of the ammonia water is 20-30%.
[0028] In some embodiments, the film-forming agent is selected from potassium sodium tartrate, preferably potassium sodium tartrate tetrahydrate.
[0029] In some embodiments, the dispersant is selected from polyvinylpyrrolidone (PVP).
[0030] In some embodiments, the molar ratio of the buffer to the film-forming agent is 1:50-2:1, for example, 1:40, 1:20, 1:10, 1:5, 1:2, 1:1.5, 1:1, 2:1 or any value therebetween.
[0031] In some embodiments, the molar ratio of the dispersant to the film-forming agent is 0.01-0.5, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5 or any value therebetween.
[0032] In some embodiments, the mass ratio of the pH adjuster to the first metal is 1:10-1:1, for example, 1:8, 1:5, 1:3, 1:2, 1:1 or any value therebetween.
[0033] In some embodiments, the mass ratio of the pH adjuster to the first metal is 1:8-1:2.
[0034] In some embodiments, the method for preparing the solution containing the second metal compound comprises the following steps: mixing the second metal compound with deionized water to obtain an aqueous solution containing the second metal compound; and then subjecting the aqueous solution containing the second metal compound to a reduction reaction with a reducing agent.
[0035] In some embodiments, the molar ratio of the first metal to the film-forming agent is (0.5-10):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value therebetween.
[0036] In some embodiments, the molar ratio of the first metal to the film-forming agent is (1-8):1.
[0037] In some embodiments, the reducing agent is selected from one or more of aqueous ammonia, ethylene glycol, glycerol or glucose.
[0038] In some embodiments, the mass concentration of the ammonia water is 20-30%.
[0039] In some embodiments, the weight ratio of the reducing agent to the second metal compound is 10:1-1:3, for example, 9:1, 7:1, 5:1, 3:1, 1:1, 1:2, 1:3 or any value therebetween.
[0040] In some embodiments, the weight ratio of the reducing agent to the second metal compound is 5:1-1:2.
[0041] In some embodiments, the power of the microwave treatment is greater than or equal to 500W, preferably greater than or equal to 750W, more preferably 1000-8000W, such as 1000-3000W.
[0042] In a third aspect, the present invention provides an application of the metal composite material described in the first aspect in the field of conductive materials, semiconductors or photovoltaics.
[0043] The metal composite material of the invention has more uniform coating, lower resistance and better chemical stability at high temperature.
[0044] The invention utilizes microwave electromagnetic field effect to improve the conductivity and stability of the metal composite material. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0046] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods. Example 1
[0047] (1) Take a beaker / glass bottle 1) and disperse 3 g of spherical copper powder in 50 mL of deionized water by ultrasonication for 5 min; (2) 0.71 g of ammonium sulfate and 1.41 g of ammonia water (drawn and added dropwise using a syringe) were added sequentially, ultrasonicated for 1 min, and then stirred at room temperature on a magnetic stirrer for 10 mins; (3) Add 1.13 g of potassium sodium tartrate tetrahydrate and 0.12 g of PVP, ultrasonicate for 1 min, and stir at room temperature on a magnetic stirrer for 10 mins; (4) Take another beaker / glass bottle 2), add 0.8 g of silver nitrate to 15 mL of deionized water, and stir on a magnetic stirrer at room temperature for 10 mins to dissolve; (5) Add 0.92 g of reducing agent (ammonia water) dropwise into the silver nitrate solution while stirring to obtain a silver-containing solution; (6) Add the silver solution in beaker / glass bottle 2) dropwise to the suspension of copper powder in beaker / glass bottle 1), and control the dropping process to be about 5 minutes, during which magnetic stirring is performed; (7) Immediately after the addition, the mixed solution was poured into a quartz boat and placed in a microwave reactor; (8) After sealing the microwave reactor, check the air tightness of the device; first adjust the flow meter at the bottom of the preheating furnace to 300 mL / min and detect the bubbles in the tail gas bottle, then adjust the flow meter to 30 mL / min to observe the bubble situation. If bubbles come out, it is considered that the air tightness of the entire device is good, and the device can be purged to replace the air in the device with nitrogen. After the device is purged, adjust the flow meter to 100 mL / min; (9) Turn on the microwave reactor; set the reaction power to 1000W and the reaction temperature to 250℃-300℃. After reacting for 60 minutes under this condition, turn off the microwave reactor, and take out the material after the reactor cools to room temperature to obtain a silver-coated copper composite powder material. The prepared powder material was tested for resistivity, resistivity after calcination at 200℃ for 15 minutes and cooling, and weight. The specific test results are shown in Table 1. Embodiment 2-4
[0048] The difference between Example 2 to Example 4 and Example 1 is that different masses of silver nitrate are used, and the test results of the prepared powder materials are shown in Table 1.
[0049]
[0050] The mass content of silver in Table 1 refers to the percentage of the mass of silver to the total mass of the metal composite material.
[0051] It can be seen from Table 1 that as the mass content of silver decreases, the resistivity increases. Example 5 to Example 7
[0052] The difference between Examples 5 to 7 and Example 1 is that the reactor power is controlled, the reaction temperature is maintained at 40°C, 60°C, and 80°C, the reaction is carried out for 1 hour (including the heating time), and then the mixture is taken out and centrifuged for impurity removal 3 times (4000rpm 5min). After each centrifugation, the insoluble matter is redispersed in anhydrous ethanol until the supernatant is colorless and transparent, and then dried in a vacuum drying oven at 80°C for 4 hours. The test results of the prepared powder material are shown in Table 2.
[0053]
[0054] As can be seen from Table 2, the present invention can obtain metal composite materials with good performance by microwave treatment at low temperature and high temperature, and has low requirements on reaction conditions. Example 8 to Example 10
[0055] The difference between Examples 8 to 10 and Example 1 is that the same mass of ethylene glycol, propylene glycol or glucose is used instead of the reducing agent (ammonia water). The test results of the prepared powder materials are shown in Table 3.
[0056]
[0057] It can be seen from Table 3 that using different reducing agents to treat the second metal can obtain metal composite materials with good performance and low requirements for reaction raw materials. Among them, ammonia water and ethylene glycol as reducing agents can make the material have a lower resistivity. Example 11 to Example 16
[0058] The difference between Example 11 to Example 16 and Example 1 is that different types of metal / non-metal powders are selected for silver coating (see Table 4 for details). The test results of the prepared powder materials are shown in Table 4.
[0059]
[0060] It can be seen from Table 4 that when the first metal is a non-metallic material, the resistivity becomes significantly larger. Example 17 to Example 20
[0061] The difference between Example 17 to Example 20 and Example 1 is that different types of metals (same molar mass) are selected to coat the copper powder (see Table 5 for details). The test results of the prepared powder materials are shown in Table 5.
[0062] Comparative Examples 1-3
[0063] The difference between Comparative Examples 1 to 3 and Example 1 is that microwaves are not turned on during the reaction, and the reactor temperature is brought to the required temperature range only by electrical heating (see Table 6 for details). The test results of the prepared powder materials are shown in Table 6.
[0064]
[0065] According to Table 6, when the microwave treatment is not used in Comparative Examples 1-3, even if the temperature is increased, the resistivity of the powder, especially the resistivity of the powder after calcination at 200° C., is significantly higher than the resistivity obtained by microwave treatment in Example 1.
[0066] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A metal composite material, comprising a first metal and a second metal coated on a surface of the first metal; In the metal composite material, the mass content of the second metal is 3-70%; The mass ratio of the second metal to the first metal is 0.01-2.
2. The metal composite material according to claim 1, characterized in that: The resistivity of the metal composite material is 15-70 μΩ·cm, The resistivity of the metal composite material after being burned at 200° C. is 15-100 μΩ·cm.
3. The metal composite material according to claim 1, characterized in that: The first metal is selected from one or more of aluminum, zinc, nickel, bismuth or copper; and / or The second metal is selected from one or more of nickel, zinc, manganese, gold or silver.
4. A method for preparing the metal composite material according to any one of claims 1 to 3, comprising the steps of: coating an aqueous solution containing a first metal and a solution containing a second metal compound under microwave treatment, The second metal compound is selected from one or more of the nitrate, nitrite, sulfate, sulfoxylate, chlorate, hypochlorite, perchlorate, acetate, carbonate, bicarbonate, oxalate, aluminate, silicate, metasilicate, chloride, sulfide, oxide or hydroxide of the second metal; The mass ratio of the second metal compound to the first metal is 0.01-2.
5. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: S1, mixing an aqueous solution containing a first metal, a dispersant, a buffer, a pH adjuster, and a film-forming agent to obtain a suspension; S2, mixing a solution containing a second metal compound, a reducing agent and the suspension and subjecting the mixture to microwave treatment.
6. The preparation method according to claim 5, characterized in that: The buffer is selected from ammonium sulfate; The pH regulator is selected from ammonia water; The film-forming agent is selected from potassium sodium tartrate; The dispersant is selected from polyvinyl pyrrolidone.
7. The preparation method according to claim 5, characterized in that: The molar ratio of the buffer to the film-forming agent is 1:50-2:1; The molar ratio of dispersant to film-forming agent is 0.01-0.5; The mass ratio of the pH adjuster to the first metal is 1:10-1:1; The molar ratio of the first metal to the film-forming agent is (0.5-10):
1.
8. The preparation method according to claim 5, characterized in that: The reducing agent is selected from one or more of ammonia, ethylene glycol, glycerol or glucose; The weight ratio of the reducing agent to the second metal compound is 10:1-1:
3.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The power of the microwave treatment is greater than or equal to 500W.
10. Use of the metal composite material according to any one of claims 1 to 3 or the metal composite material prepared by the preparation method according to any one of claims 4 to 9 in the field of batteries, conductive materials, semiconductors or photovoltaics.
Citation Information
Patent Citations
Preparation method of copper-silver composite powder
CN102161104A
Nanoscale silver covered copper composite wire and preparing method and application thereof
CN107303609A
Preparation method of core-shell structure metal composite material
CN114378299A
Cobalt modified silver coated copper composite material and preparation method thereof
CN116352083A
Method for producing metal nanoparticle, silver / copper nanoparticle, and electrically conductive paste
JP2008248298A
